Modulation of the Eelgrass – Labyrinthula zosterae Interaction Under Predicted Ocean Warming, Salinity Change and Light Limitation - Brakel, Janina; Jakobsson-Thor, Stina; Bockelmann, Anna-Christina; Reusch, Thorsten B. H. (Frontiers in Marine Science, 2019)
Marine infectious diseases can have large-scale impacts when they affect foundation species such as seagrasses and corals. Interactions between host and disease, in turn, may be modulated by multiple perturbations associated with global change. A case in point is the infection of the foundation species Zostera marina (eelgrass) with endophytic net slime molds (Labyrinthula zosterae), the putative agent of eelgrass wasting disease that caused one of the most severe marine pandemics across the North-Atlantic in the 1930s. The contemporary presence of L. zosterae in many eelgrass meadows throughout Europe raises the question whether such a pandemic may re-appear if coastal waters become more eutrophic, warmer and less saline. Accordingly, we exposed uninfected Baltic Sea Z. marina plants raised from seeds to full factorial combinations of controlled L. zosterae inoculation, heat stress, light limitation (mimicking one consequence of eutrophication) and two salinity levels. We followed eelgrass wasting disease dynamics, along with several eelgrass responses such as leaf growth, mortality and carbohydrate storage, as well as the ability of plants to chemically inhibit L. zosterae growth. Contrary to our expectation, inoculation with L. zosterae reduced leaf growth and survival only under the most adverse condition to eelgrass (reduced light and warm temperatures). We detected a strong interaction between salinity and temperature on L. zosterae abundance and pathogenicity. The protist was unable to infect eelgrass under high temperature (27°C) in combination with low salinity (12 psu). With the exception of a small positive effect of temperature alone, no further effects of any of the treatment combinations on the defense capacity of eelgrass against L. zosterae were detectable. This work supports the idea that contemporary L. zosterae isolates neither represent an immediate risk for eelgrass beds in the Baltic Sea, nor a future one under the predicted salinity decrease and warming of the Baltic Sea.